2004
DOI: 10.1111/j.1365-2222.2004.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of recombinant dog allergens Can f 1 and Can f 2 for the diagnosis of dog allergy

Abstract: The recombinant allergens can be used reliably to identify Can f 1 and Can f 2-sensitized individuals. However, the two allergens are insufficient as reagents for diagnosing dog allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 26 publications
(34 reference statements)
2
68
0
Order By: Relevance
“…The study included 25 allergic patients whose allergy to dog was confirmed at the Pulmonary Clinic of Kuopio University Hospital, as described in detail elsewhere (12). For a person to be classified as dog-allergic, the following criteria were adopted: specific IgE by the dog UniCAP fluoroenzyme-immunometric assay (Pharmacia) of Ͼ0.7 kU/l and a skin prick test (SPT) 3 with dog allergen (epithelial preparation from ALK Abelló) of Ն3 mm.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study included 25 allergic patients whose allergy to dog was confirmed at the Pulmonary Clinic of Kuopio University Hospital, as described in detail elsewhere (12). For a person to be classified as dog-allergic, the following criteria were adopted: specific IgE by the dog UniCAP fluoroenzyme-immunometric assay (Pharmacia) of Ͼ0.7 kU/l and a skin prick test (SPT) 3 with dog allergen (epithelial preparation from ALK Abelló) of Ն3 mm.…”
Section: Subjectsmentioning
confidence: 99%
“…One of the subjects who had clinical symptoms upon exposure to dog and a positive SPT with dog allergen had no measurable IgE Ab to dog. Thirteen of the dog-allergic subjects were found to be sensitized to Can f 1 by SPTs with rCan f 1, as described previously (12). Twelve randomly selected healthy nonatopic dog owners served as control subjects.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast P. pastoris has been used to express many allergens (Barral et al 2004;Saarelainen et al 2004;Barderas et al 2005). Because P. pastoris secretes few of its own proteins, recombinant proteins extracted from the medium are less contaminated with endogenous e-mail: Marcie_Moehnke@baylor.edu.…”
Section: Introductionmentioning
confidence: 99%
“…Can f 1 is more allergenic than Can f 2: 70% of the patients showed positive allergenic signals to Can f 1, but only 20% of the patients reacted to Can f 2 [6]. Recent research in Finland showed that the allergenic dominancy of Can f 1 was not found [8]. …”
Section: Introductionmentioning
confidence: 99%